2016
DOI: 10.1139/cjas-2016-0133
|View full text |Cite
|
Sign up to set email alerts
|

Maize replacement with sorghum and a combination of protease, xylanase and phytase on performance, nutrient utilization, litter moisture and digestive organ size in broiler chicken

Abstract: Abstract:We investigated the effects of a combination of protease, xylanase, and phytase in maize-or sorghum-based diets for broilers. Two experiments were conducted with male chicks randomly distributed in a 3 × 2 factorial arrangement with three replacement levels of maize with sorghum (0%, 50%, and 100%) with or without enzymes. In the first trial, 1152 chicks were allotted to 36 floor pens to determine performance, relative organ weight, and litter moisture. A second trial was performed with 150 and 120 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
3
0
3
Order By: Relevance
“…In the treatment containing sorghum + 9% RASM, feed conversion values were similar to those obtained for corn-based diets. Sorghum contains tannins (low level), phytate, kafirin, and polyphenols that may have anti-nutritional effects (McCuistion et al, 2018), causing lower digestibility and nitrogen retention rates (Pasquali et al, 2017) relative to cornbased diets. However, these effects may have been mitigated by a lower ratio of sorghum and higher oil level relative to corn-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment containing sorghum + 9% RASM, feed conversion values were similar to those obtained for corn-based diets. Sorghum contains tannins (low level), phytate, kafirin, and polyphenols that may have anti-nutritional effects (McCuistion et al, 2018), causing lower digestibility and nitrogen retention rates (Pasquali et al, 2017) relative to cornbased diets. However, these effects may have been mitigated by a lower ratio of sorghum and higher oil level relative to corn-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…Nalle et al [6] suggested that it is possible to include high levels of lupine in diets for broilers by removing the hull and/or by using enzymes to degrade NSP. The use of exogenous enzymes such as xylanases and proteases in diets for broilers to attenuate nutrient encapsulation by NSP, such as arabinoxylans, and to increase protein degradation has recently been investigated [8]. We hypothesized that inclusion of dehulled lupine seed as the main protein source plus enzymes in broiler diets does not affect productive performance, size of digestive organs or welfare-related variables.…”
Section: Introductionmentioning
confidence: 99%
“…Nadeem et al (2005) melaporkan bahwa penambahan enzim dalam ransum ayam broiler menurunkan bobot hati, sedangkan Hussein et al (2020) Mohammadigheisar et al (2018) melaporkan sebaliknya bahwa penambahan enzim pada ransum ayam broiler yang mengandung energi rendah akan meningkatkan bobot hati, hal ini karena berkaitan dengan aktivitas hati yang lebih tinggi dalam metabolisme lemak menjadi energi (Mohammadigheisar et al, 2018). Roofchaei et al (2019), Pasquali et al (2017), Zhu et al (2014), Sharifi et al (2012), Hajati (2010), serta Sinurat et al (2022) melaporkan bahwa supplementasi enzim tidak mempengaruhi bobot hati. Penelitian ini memperlihatkan bobot relative hati tidak dipengaruhi oleh penambahan cairan rumen kerbau sebagai sumber enzim, dengan hasil yang sama seperti yang dilaporkan oleh Roofchaei et al (2019), Pasquali et al (2017) serta Zhu et al (2014), Sharifi et al (2012), Hajati (2010) serta Sinurat et al (2022).…”
Section: Bobot Organ Asesoris Dan Organ Pencernaanunclassified
“…Roofchaei et al (2019), Pasquali et al (2017), Zhu et al (2014), Sharifi et al (2012), Hajati (2010), serta Sinurat et al (2022) melaporkan bahwa supplementasi enzim tidak mempengaruhi bobot hati. Penelitian ini memperlihatkan bobot relative hati tidak dipengaruhi oleh penambahan cairan rumen kerbau sebagai sumber enzim, dengan hasil yang sama seperti yang dilaporkan oleh Roofchaei et al (2019), Pasquali et al (2017) serta Zhu et al (2014), Sharifi et al (2012), Hajati (2010) serta Sinurat et al (2022). Diduga bobot hati lebih banyak dipengaruhi senyawa anti nutrisi dalam pakan karena fungsi hati adalah menetralis senyawa-senyawa toksik yang masuk kedalam tubuh ayam broiler.…”
Section: Bobot Organ Asesoris Dan Organ Pencernaanunclassified